A political economy of attention, mindfulness and consumerism: reclaiming the mindful commons - Doran, Peter (Routledge studies in sustainability, 2017)
Towards a "mindful commons" : the anthropocene and the attention revolution -- The spirit of activism : non-violence as a way of life -- The Cartesian legacy -- Foucault, Zen and the art of challenging consumerism -- Conclusions : attention deficit and ecological degradation advance together